Empirical Analysis of the Impact of Smart Economy Through Entrepreneurial Credit Program ( KURNIA ) on Empowering SMEs in Kediri City - Muhammad M. Haki Al-Arif; Dwi Wulandari; Inayati Dwi Putri (East Asian Journal of Multidisciplinary Research, 2023)
In today's globalized world, Information Technology (IT) is advancing rapidly, with a strong public interest in information systems. Information Technology (IT) helps governments and organizations process data effectively. The goal of the Smart Economy is to create an ecosystem supporting local economies and adapting to disruptions. To achieve this, financial literacy programs are essential, focusing on three elements: ecosystem, community welfare improvement, and financial transactions. The strategy emphasizes a creative and cooperative industrial environment, benefiting all parties, which ultimately enhances people's well-being. The "KURNIA" initiative offers low-interest business capital loans, benefiting micro-businesses and cooperatives, especially during the COVID-19 pandemic. This quantitative study explores the causal relationship between the KURNIA program and the empowerment of MSMEs in Kediri City, confirming a significant positive impact.